Contained Rupture of an Abdominal Aortic Aneurysm With Extensive Vertebral Body and Retroperitoneal Space Destruction. Issue 5 (September 2017) - Walker, Sean T.; Pipinos, Iraklis I.; Johanning, Jason M.; Vargo, Christopher J.
Abstract : Abstract: Chronic contained rupture of an abdominal aortic aneurysm with vertebral body erosion most commonly presents with symptoms of low back pain. Although not well known, vertebral body erosion or destruction may be seen in up to 25% of patients with sealed or contained rupture of an abdominal aortic aneurysm. This appearance on cross-sectional imaging may mimic a malignant or infectious process. Although these cases can present a diagnostic challenge, published cases of chronic contained rupture of an abdominal aortic aneurysm with vertebral body erosion demonstrate clinical and imaging similarities that, when recognized, can assist in diagnosis.